AN OUTLIER DETECTION METHOD IN GEODETIC NETWORKS BASED ON THE ORIGINAL OBSERVATIONS - Erdogan, Bahattin (UNIV FEDERAL PARANA, CENTRO POLITECNICO, 2014)
The observations in geodetic networks are measured repetitively and in the network adjustment step, the mean values of these original observations are used. The mean operator is a kind of Least Square Estimation (LSE). LSE provides optimal results when random errors are normally distributed. If one of the original repetitive observations has outlier, the magnitude of this outlier will decrease because the mean value of these original observations is used in the network adjustment and outlier detection. In this case, the reliability of the outlier detection methods decreases, too. Since the original repetitive observations are independent, they can be used in the adjustment model instead of the estimating mean value of them. In this study, to show the effects of the estimating mean value of the original repetitive observations, a leveling network that contains both outward run and backward run observations were simulated. Tests for outlier, Huber and Danish methods were applied to two different cases. First, the mean values of the original observations (outward run and return run) were used; and then all original observations were considered in the outlier detection. The reliabilities of the methods were measured by Mean Succes Rate. According to the obtained results, the second case has more reliable results than first case.
Keywords: Outlier Detection; Original Observations; Tests for Outlier; Robust Method; Reliability; ROBUST METHODS; TESTS; Geochemistry & Geophysics; Remote Sensing